Multivariate analysis of FcR-mediated NK cell functions identifies unique clustering among humans and rhesus macaques - Tuyishime, Marina; Spreng, Rachel L.; Hueber, Brady; Nohara, Junsuke; Goodman, Derrick; Chan, Cliburn; Barfield, Richard; Beck, Whitney E.; Jha, Shalini; Asdell, Stephanie; Wiehe, Kevin; He, Max M.; et al. (Frontiers in Immunology, 2023)
Rhesus macaques (RMs) are a common pre-clinical model used to test HIV vaccine efficacy and passive immunization strategies. Yet, it remains unclear to what extent the Fc-Fc receptor (FcR) interactions impacting antiviral activities of antibodies in RMs recapitulate those in humans. Here, we evaluated the FcR-related functionality of natural killer cells (NKs) from peripheral blood of uninfected humans and RMs to identify intra-and inter-species variation. NKs were screened for FcgRIIIa (human) and FcgRIII (RM) genotypes (FcgRIII(a)), receptor signaling, and antibodydependent cellular cytotoxicity (ADCC), the latter mediated by a cocktail of monoclonal IgG1 antibodies with human or RM Fc. FcgRIII(a) genetic polymorphisms alone did not explain differences in NK effector functionality in either species cohort. Using the same parameters, hierarchical clustering separated each species into two clusters. Importantly, in principal components analyses, ADCC magnitude, NK contribution to ADCC, FcgRIII(a) cell-surface expression, and frequency of phosphorylated CD3ζ NK cells all contributed similarly to the first principal component within each species, demonstrating the importance of measuring multiple facets of NK cell function. Although ADCC potency was similar between species, we detected significant differences in frequencies of NK cells and pCD3ζ+ cells, level of cell-surface FcgRIII(a) expression, and NK-mediated ADCC (P<0.001), indicating that a combination of Fc-FcR parameters contribute to overall inter-species functional differences. These data strongly support the importance of multi-parameter analyses of Fc-FcR NK-mediated functions when evaluating efficacy of passive and active immunizations in pre-and clinical trials and identifying correlates of protection. The results also suggest that pre-screening animals for multiple FcRmediated NK function would ensure even distribution of animals among treatment groups in future preclinical trials.